Stochastic Delay Population Dynamics under Regime Switching: Global Solutions and Extinction - Zheng Wu; Hao Huang; Lianglong Wang (Abstract and Applied Analysis)
This paper is concerned with a delay Lotka-Volterra model under regime switching diffusion in random environment. By using generalized Itô formula, Gronwall inequality and Young’s inequality, some sufficient conditions for existence of global positive solutions and stochastically ultimate boundedness are obtained, respectively. Finally, an example is given to illustrate the main results.